Low Doses of Etanercept Can Be Effective to Maintain Remission in Psoriatic Arthritis Patients. Issue 3 (April 2018) - de Stefano, Renato; Frati, Elena; de Quattro, Davide; de Stefano, Ludovico
Abstract : Objectives: We realized a longitudinal open-label study to determine if increasing intervals between etanercept (ETN) administration could be effective in maintaining remission with a stable dose in a patient population affected by psoriatic arthritis (PsA) who had achieved sustained remission with ETN 25 mg biweekly. Methods: Fifty-four PsA patients were recruited at the Rheumatology Unit of Azienda Ospedaliera Universitaria Senese. Patients, who were in clinical sustained remission with biweekly ETN 25 mg at weeks 12 and 16, and were switched to a weekly regimen. If clinical remission persists at weeks 24 and 28, patients were switched to an every-other-week regimen, continuing with this administration schedule for the entire duration of the study if at weeks 36 and 40 clinical remission was maintained. If, on the contrary, in one of the check there was an increase in disease activity, the therapeutic scheme returned to the previous one. Results: The results of our study indicate that a consistent percentage (72%) of subjects with PsA, achieving a sustained remission with ETN 25 mg biweekly, maintains a remission, after a year of starting therapy, despite a progressive dose reduction by an increase in the dosing interval, 21% with a weekly regimen and 51% with an every-other-week regimen. Conclusions: Our results show that the main reasons that hinder the dosing interval increase in ETN in PsA patients in sustained clinical remission at standard doses are peripheral polyarthritis pattern and exacerbation of cutaneous manifestations.